Irisin Contributes to Neuroprotection by Promoting Mitochondrial Biogenesis After Experimental Subarachnoid Hemorrhage - Tu, Tianqi; Yin, Shigang; Pang, Jinwei; Zhang, Xianhui; Zhang, Lifang; Zhang, Yuxuan; Xie, Yuke; Guo, Kecheng; Chen, Ligang; Peng, Jianhua; Jiang, Yong (Frontiers in Aging Neuroscience, 2021)
Subarachnoid hemorrhage (SAH) is a devastating form of stroke, which poses a series of intractable challenges to clinical practice. Imbalance of mitochondrial homeostasis has been thought to be the crucial pathomechanism in early brain injury (EBI) cascade after SAH. Irisin, a protein related to metabolism and mitochondrial homeostasis, has been reported to play pivotal roles in post-stroke neuroprotection. However, whether this myokine can exert neuroprotection effects after SAH remains unknown. In the present study, we explored the protective effects of irisin and the underlying mechanisms related to mitochondrial biogenesis in a SAH animal model. Endovascular perforation was used to induce SAH, and recombinant irisin was administered intracerebroventricularly. Neurobehavioral assessments, TdT-UTP nick end labeling (TUNEL) staining, dihydroethidium (DHE) staining, immunofluorescence, western blot, and transmission electron microscopy (TEM) were performed for post-SAH assessments. We demonstrated that irisin treatment improved neurobehavioral scores, reduced neuronal apoptosis, and alleviated oxidative stress in EBI after SAH. More importantly, the administration of exogenous irisin conserved the mitochondrial morphology and promoted mitochondrial biogenesis. The protective effects of irisin were partially reversed by the mitochondrial uncoupling protein-2 (UCP-2) inhibitor. Taken together, irisin may have neuroprotective effects against SAH via improving the mitochondrial biogenesis, at least in part, through UCP-2 related targets.